Türkiye'nin iki farklı coğrafik bölgesinde yaşayan cinsel istismar mağdurlarınsosyodemografik ve istismara ait özelliklerin karşılaştırılması - (:unkn) unknown (My University, 2014)
Amaç: Bu araştırmada Antalya ve Diyarbakır üniversite hastanelerine başvuran cinsel istismar mağduru çocukların sosyodemografik ve istismara ait verilerinin karşılaştırılması amaçlanmıştır.Yöntem: Akdeniz Üniversitesi Çocuk ve Ergen Ruh Sağlığı ve Hastalıkları (ÇERSH) polikliniğine 2010 yılı içerisinde başvuran, 4-17 yaş aralığında 172 çocuk ve Dicle Üniversitesi ÇERSH polikliniğine 2012 yılı içerisinde başvuran, 4-17 yaş aralığında 167 çocuk çalışmaya alınmıştır. Olguların sosyodemografik ve istismara ait verileri hasta dosyalarının geriye dönük taranması ile elde edilmiştir.Bulgular: Diyarbakır grubunda çocuğun eğitim yılı, annenin eğitim yılı ve babanın eğitim yılı anlamlı oranda düşük iken kardeş sayısı ortalaması anlamlı oranda yüksekti. Diyarbakır grubunda erkek mağdur oranı anlamlı derecede yüksekti. Anne babanın sağ ve beraber olduğu aile yapısı Diyarbakır grubunda anlamlı oranda yüksekti. Penetrasyon varlığı ve istismarcıya yakınlık açısından gruplar arasında fark saptanmadı. Sonuç: Bu çalışma ile Türkiye'nin sosyokültürel, ekonomik ve etnik bakımdan farklılıklar gösteren iki bölgesi (Akdeniz ve güneydoğu Anadolu) arasındaki cinsel istismar mağdurlarının özellikleri araştırılmıştır. Bu çalışma bize Türkiye'de bölgeler arasında cinsel istismarın sosyodemografik ve istismara ait özelliklerinin bir kısmının farklı olduğu göstermiştir. Cinsel istismarı önleme çalışmalarının bu bulguların ışığında tekrar yapılandırılması gerektiği kanaatindeyiz. Örneğin, Güneydoğu Anadolu'da çocuk işçiliğinin önlenmesi, bireylerin okuryazarlık oranlarının arttırılması ve aile planlaması uygulamalarının yaygınlaştırılması öncelikli hedefler olmalıdır.

Objective: The aim of this study is to compare the sociodemographic and abuse-related data of the children who have presented to the Antalya and Diyarbakir University hospitals due to sexual abuse.Method: The patient files of 172 children between the ages of 4-17 presented to the Akdeniz University, Department of Child and Adolescent Psychiatric Health and Diseases (CAPHD) Clinic within the year 2010, and of 167 children between the ages of 4-17 presented to the Dicle University CAPHD Clinic during the year 2012 were scanned and the sociodemographic and abuse-related data of the patients were recorded.Results: In the Diyarbakir group, the total years of education of the child, the total years of education of the mother, and the total years of education of the father were significantly lower, while the mean number of the siblings was significantly higher. The number of the male abuse survivors in the Diyarbakir group was significantly higher. The family structure where the parents are alive and living together was significantly more frequent in the Diyarbakir group. No difference in terms of the occurrence of penetration and relationship with the abuser was observed between the groups. Conclusion: Within the framework of this study, the characteristics of the survivors of abuse between two socioculturally, economically and ethnically different regions of Turkey (the Mediterranean region and the south-east Anatolian region) have been investigated. This study has demonstrated that some of the sociodemographic and abuse-related characteristics of sexual abuse in Turkey differs between these regions. We are of the opinion that efforts to prevent sexual abuse should be restructured in the light of these results. For instance, prevention of child labour, increasing the literacy rate of the individuals and promoting family planning efforts in south-east Anatolia should be the primary focus of these efforts.
Comparison of Sexual Abuse Survivors From Two Different Geographical Regions of Turkey in Terms of the Sociodemographic and Abuse-Related Characteristics